Prosthodontic Rehabilitation of Patients with Bell’s Palsy: Our Experience - Rajapur, Anand (J Int Oral Health, 2015)
Bell’s palsy is an idiopathic unilateral lower motor neuron paresis or paralysis of the facial nerve of sudden onset. It involves loss of muscular control on the affected side of the face. This paper reports the prosthodontic management of patients with Bell’s palsy and also describes a technique to stabilize the jaw movements in complete denture patients using interim dentures. A 65-year-old male edentulous patient and a 55-year-old female edentulous patient reported to the department of prosthodontics to get their missing teeth replaced. They both gave history of facial paralysis and were diagnosed for Bell’s palsy. Interim training dentures with flat occlusal tables were fabricated first to correct and stabilize their mandibular movements. During initial 4 weeks, there was poor functioning of the interim dentures. Gradually by 8(th) week the patients started stabilizing the interim dentures and were functional. After observing the improvement when the patients had no pain and could stabilize and use the treatment dentures successfully, definitive complete dentures were fabricated. This case report presents a systematic approach to successively rehabilitate edentulous patients with Bell’s palsy.